Outbreak of acute febrile respiratory illness caused by human adenovirus B P14H11F14 in a military training camp in Shandong China - Dongliu, Yuan (Arch Virol, 2016)
This study reports an outbreak of acute febrile respiratory illness caused by human adenovirus B [P14H11F14] in a military training center in China between May and June 2014. In total, 164 military personnel were affected, and two patients were admitted into the intensive care unit of the military regional central hospital. A HAdV-B [P14H11F14] virus was confirmed as the etiological pathogen of this acute outbreak of febrile respiratory illness based on clinical manifestations, epidemiological characteristics, specific molecular detection results, phylogenetic analysis, and serological assays. The virus was isolated by the rhabdomyosarcoma cell culture method, and the complete sequences of the E1A, penton base, hexon, and fiber genes were determined and deposited in the GenBank database. Phylogenetic and sequence homology analyses indicated that the isolated strain is most closely related to some HAdV-55 strains from mainland China. However, this strain appeared to be less virulent than former HAdV-55 strains. According to the chest X-ray results of 31 affected patients, there was no radiological evidence of pneumonia. The most frequent symptoms in these patients were sore throat (95.12 %, 156/164) and tonsillitis (93.29 %, 153/164). During the course of the outbreak, incorrect response measures and some potential risk factors, such as fire training and marching training, may have exacerbated the spread of the infection. This outbreak illustrates the urgent need to improve the epidemiological and etiological surveillance of HAdV infections and to improve the ability of doctors and health officials in basic units of the Chinese army to respond effectively to febrile respiratory illness.